The Ethics of Advertising in Islamic Economics - Muhammad Taufiq Affandi (University of Darussalam Gontor, 2012)
Advertising is the huge weapon of manufacturers located in frontier to campaign their product. Capitalist has been—for a very long time—spending a great amount of money in advertising. They believe that advertising can not be separated from their economic activities. Capitalists, therefore, use all means to make attractive advertisement. They raced to produce a unique and interested advertisement. Soon, advertising has lost its real function to give information of product to consumer. Further, there are so many advertising activities which break the norms. They show part of body that should not be visible. Some other use rude words and jokes. Others are provocation to use dangerous items. Frequently, some advertising insult other product, or other race. Those are all harmful for people, especially for Muslim.